Policy and epistemologial aspects of the foundations of communication research in Brazil - Sá Martino, Luís Mauro (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
This paper outlines the relationship between academic policy and the epistemological foundations of Communication studies, drawing on bibliographical research. The text creates a studies between these elements, and aims to hightlight the political and professional demand for Communication Studies when it was first established as an research area. This is not claiming that policy has determined the scientific. The goal is to highlight the resonance of political matters on communication Studies, particularly the gap between its institutional and epistemological aspects: Communication is a well-established academic degree, but it still lacks some epistemological foundations. The paper also argues that the current epistemological debate on Communication may put both aspects apace.